Cash is king: the balance of costs and effectiveness of treatments for actinic keratosis. (5th April 2020) - Steeb, T.; Heppt, M.V.; Berking, C.
Abstract : Linked Article: Jansen et al. Br J Dermatol 2020; 183 :738–744 .